Composite dietary antioxidant index and sleep health: a new insight from cross-sectional study - Bingquan Xiong; Jiaxin Wang; Rui He; Guangsu Qu (BMC Public Health, 2024)
Abstract Background Low-quality sleep and obstructive sleep apnea (OSA) can result in series of chronic diseases. Healthy diet has been considered as an effective and simple strategy to optimize sleep quality. However, current evidence on the correlation of dietary composite antioxidant intake with sleep health remained obscure. Aim of the study To determine the relationship of composite dietary antioxidant index (CDAI) and sleep health. Methods Cross-sectional analyses were based on National Health and Nutrition Examination Survey (NHANES) 2005–2008. Dietary consumption was assessed by trained staff using 24-h diet recall method and CDAI was calculated based on previous validated approach that included six antioxidants. Sleep-related outcomes were self-reported by a set of questionnaires and classified into OSA, day sleepiness, and insufficient sleep. Weighted logistic regression was conducted to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Restricted cubic spline (RCS) regressions were also used to evaluate the dose-response of CDAI and three sleep-related outcomes. Results A total of 7274 subjects included (mean age: 46.97 years) were enrolled in our study, including 3658 were females (52.54%) and 3616 were males (47.46%). Of them, 70.6%, 29.51%, and 35.57% of the subjects reported that they had OSA, day sleepiness and insufficient sleep, respectively. Logistic regression showed the highest quartile of CDAI was inversely associated with the risk of OSA (OR: 0.69, 95%CI: 0.49–0.97), day sleepiness (OR: 0.64, 95%CI: 0.44–0.94) and insufficient sleep (OR: 0.68, 95%CI: 0.50–0.92) compared with the lowest quartile. RCS showed linear relationship of CDAI and insufficient sleep but non-linear relationship of CDAI with OSA and day sleepiness. Conclusions Our results show that CDAI was non-linearly associated with lower risk of OSA and day sleepiness whereas a linear inverse association between CDAI and insufficient sleep was observed. These findings implicate that combined intake of antioxidants could be a promising and effective approach to optimize sleep quality for public.